The Effect of Product Quality and Service Quality on Purchasing Decisions Through Purchase Intention as an Intervening Variable (Study on Consumers of Cempaka Trowulan Batik) - Ryan Bagus Priadi; Nersiwad; Kasnowo (CV Putra Publisher, 2023)
The purpose of this research is to determine the effect of product quality and service quality on purchasing decisions through purchase intention as an intervening variable in UMKM Batik Cempaka. The method used in this study is a quantitative method with descriptive analysis based on primary data obtained from questionnaires and secondary data obtained from related parties, interviews, books and journals, etc. This research was conducted by distributing questionnaires to respondents. The population in this study were consumers of UMKM Batik Cempaka, with 110 samples used in this study. The sampling technique used was by using a sampling technique.purposive sampling. The results showed that product quality had a significant positive effect on the buying interest of UMKM Batik Cempaka consumers. Then, the quality of service has a significant positive effect on the buying interest of UMKM Batik Cempaka consumers. Purchase intention has a significant positive effect on purchasing decisions. And there is a significant positive effect between product quality and service quality on purchasing decisions through the buying interest of UMKM Batik Cempaka consumers.